Effects of dietary lysolecithin on growth performance, serum biochemical indexes, antioxidant capacity, lipid metabolism and inflammation-related genes expression of juvenile large yellow croaker (Larimichthys crocea). Issue 128 (September 2022) - Weng, Miao; Zhang, Wencong; Zhang, Zhou; Tang, Yuhang; Lai, Wencong; Dan, Zhijie; Liu, Yongtao; Zheng, Jichang; Gao, Shengnan; Mai, Kangsen; Ai, Qinghui
Abstract: A 70-day feeding trial was conducted to investigate effects of dietary lysolecithin on growth performance, serum biochemical indexes, antioxidant capacity, lipid metabolism and inflammation-related genes expression of juvenile large yellow croaker ( Larimichthys crocea ) with initial weight of 6.04 ± 0.08 g. A formulated diet containing approximately 42% crude protein and 12.5% crude lipid was used as the control diet (CON). The other three experimental diets were formulated with supplementation of 0.2%, 0.4% and 0.6% lysolecithin based on the control diet, respectively. Results showed that weight gain rate (WGR) and specific growth rate (SGR) significantly increased in fish fed diets with lysolecithin compared with those in the control diet ( P  < 0.05). Fish fed diets with 0.4% and 0.6% lysolecithin had notably higher lipid content in muscle than that in the control diet ( P  < 0.05). When fish were fed diets with lysolecithin, serum high-density lipoprotein cholesterol (HDL-c) content was notably higher than that in the control diet ( P  < 0.05), while fish fed the diet with 0.6% lysolecithin had a significant lower serum low-density lipoprotein cholesterol (LDL-c) content than that in the control diet ( P  < 0.05). Meanwhile, serum aspartate transaminase (AST) and alanine transaminase (ALT) activities in fish fed diets with lysolecithin were remarkably lower than those in the control diet ( P  < 0.05). With the increase of dietary lysolecithin from 0.2% to 0.6%, mRNA expression of stearoyl-coenzyme A desaturase 1 ( scd1 ), diacylglycerol acyltransferase 2 ( dgat2 ) and sterol-regulatory element binding protein 1 ( srebp1 ) showed decreasing trends. Furthermore, mRNA expression of carnitine palmitoyl transferase 1 ( cpt1 ) and lipoprotein lipase ( lpl ) among each dietary lysolecithin treatment were significantly higher than those in the control diet ( P  < 0.05). In terms of inflammation, mRNA expression of tumor necrosis factor α ( tnf-α ) and interleukin-1 β ( il-1β ) were significantly down-regulated in fish fed diets with lysolecithin compared with those in the control diet ( P  < 0.05), while the mRNA expression of interleukin-10 ( il-10 ) was significantly higher than that in the control diet ( P  < 0.05). In conclusion, dietary lysolecithin could promote the growth performance, improve hepatic lipid metabolism and regulate inflammation response in juvenile large yellow croaker, and the optimal supplement level of lysolecithin was approximately 0.4% in this study. Highlights: Dietary lysolecithin could significantly improve growth performance of juvenile large yellow croaker. Diets supplemented with lysolecithin could enhance lipid metabolism and alleviate fat accumulation in liver. Lysolecithin could exert beneficial effects on antioxidant capacity and inflammation response to improve health status.